2020
DOI: 10.3847/psj/ab8e45
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for a Physical Link between Asteroids (155140) 2005 UD and (3200) Phaethon*

Abstract: In 2018, the near-Earth object (155140) 2005 UD (hereafter UD) experienced a close fly by of the Earth. We present results from an observational campaign involving photometric, spectroscopic, and polarimetric observations carried out across a wide range of phase angles (0.°7–88°). We also analyze archival NEOWISE observations. We report an absolute magnitude of H V = 17.51 ± 0.02 mag and an albedo of p V = 0.10 ± 0.02. UD has been dynamically linked to Phaethon due their sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 69 publications
3
41
0
Order By: Relevance
“…We also utilized standard star observations close in airmass (∆X < 0.1) which is the other dominant factor in this systematic error. The rotation period of 2005 UD is 5.235 hours (Devogèle et al 2020), so our October 2 and 3 observations are separated by almost exactly ∼ 4.0 rotation periods, and the September 19th and October 2nd observations are separated by slightly more than ∼ 59 rotation periods. These three separate nights of observations do not show evidence for the previously reported possible heterogeneous surface of 2005 UD (Kinoshita et al 2007), but that is perhaps unsurprising as the three sets of observations span the same ∼ 1 4 of the surface.…”
Section: Near-infrared Observations Of 2005 Udmentioning
confidence: 75%
See 1 more Smart Citation
“…We also utilized standard star observations close in airmass (∆X < 0.1) which is the other dominant factor in this systematic error. The rotation period of 2005 UD is 5.235 hours (Devogèle et al 2020), so our October 2 and 3 observations are separated by almost exactly ∼ 4.0 rotation periods, and the September 19th and October 2nd observations are separated by slightly more than ∼ 59 rotation periods. These three separate nights of observations do not show evidence for the previously reported possible heterogeneous surface of 2005 UD (Kinoshita et al 2007), but that is perhaps unsurprising as the three sets of observations span the same ∼ 1 4 of the surface.…”
Section: Near-infrared Observations Of 2005 Udmentioning
confidence: 75%
“…One avenue for further study is characterizing other small bodies thought to be dynamically associated with Phaethon and the Geminids. (155140) 2005 UD is a ∼ 1.6 km NEO with a blue reflectance spectrum (Jewitt & Hsieh 2006;Devogèle et al 2020) thought to be dynamically linked to Phaethon and the Daytime Sextantids, as well as the Geminids less directly (Kasuga et al 2005). This is a second NEO with similar (visible) reflectance properties, a very low perihelion (q = 0.16AU ), and associated with its own meteor shower, and thus is expected to be a highly valuable target for comparison with Phaethon.…”
Section: The Phaethon-geminid-complex and Paper Overviewmentioning
confidence: 99%
“…Near-Earth objects (3200) Phaethon, (155140) 2005 UD and ( 225416) 1999 YC are an exception and their common origin is very likely (e.g., Ohtsuka et al, 2006;Jewitt and Hsieh, 2006;Ohtsuka et al, 2008;Hanuš et al, 2018) despite its difficult verification by n-body integrations due to the relatively long time since their separation and the general chaoticity of NEO orbits. However, certain ancillary evidence supports the common origin scenario for this cluster, such as, highly similar spectra suggesting rare B-type taxonomic classifications for the two largest members of the cluster and the almost identical polarization properties of their surfaces (Devogèle et al, 2020). Moskovitz et al (2019) identified two probable near-Earth asteroid pairs 2015 EE7 -2015 FP124 (both members within the spectral taxonomic S-complex) and 2017 SN16 -2018 RY7 (both rare V-types) and they constrained their separation ages to < 10 4 yr.…”
Section: Introductionmentioning
confidence: 73%
“…This pipeline has been fully vetted and been used to reduce hundreds of spectra (e.g. Devogèle et al 2019;Moskovitz et al 2019;Devogèle et al 2020). All images are first bias and flat field corrected using a series of 11 individual images to construct the master bias or flat.…”
Section: Spectroscopymentioning
confidence: 99%